2016
DOI: 10.1002/acr.22894
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatology Workforce Planning in Western Countries: A Systematic Literature Review

Abstract: Heterogeneity in methods used, the period or calendar years for which the estimates were projected, and heterogeneity of variables evaluated led to disparate estimates, with results ranging from 0.7 to 3.5 rheumatologists per 100,000 population. An international initiative is needed to agree upon a common approach for a reliable estimation of manpower requirements in rheumatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Results from the literature have shown that there are only a few scientific publications dealing with workforce in rheumatology thus far (1,6,8). A current review from Dejaco et al (1) about workforce planning in Western countries, included 14 scientific publications from 5 different countries. Research was heterogeneous concerning methods, investigated time periods and variables used for the calculation of manpower requirements.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Results from the literature have shown that there are only a few scientific publications dealing with workforce in rheumatology thus far (1,6,8). A current review from Dejaco et al (1) about workforce planning in Western countries, included 14 scientific publications from 5 different countries. Research was heterogeneous concerning methods, investigated time periods and variables used for the calculation of manpower requirements.…”
Section: Discussionmentioning
confidence: 99%
“…In a report from 2012, the European Commission foresaw a substantial "gap in supply of human resources in health by 2020" 1 . Several reports, in various European countries, have tried to estimate the number of available rheumatologists (1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations